2013
DOI: 10.3892/or.2013.2813
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the expression of stem cell markers in human breast cancer reveals a correlation with clinical progression and metastatic disease in ductal carcinoma

Abstract: Abstract. The tumor stem cell theory could explain how patients with metastatic disease show clinical relapse several months after starting treatment due to the survival of a small group of cells with unique characteristics. We examined the distribution and expression of a panel of stem cell markers in human breast cancer primary tumors. Human breast tissues were processed for immunohistochemistry, and RNA was extracted for analysis by quantitative-PCR. Immunohistochemical assay revealed that CD44 was strongly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
42
1
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(47 citation statements)
references
References 20 publications
3
42
1
1
Order By: Relevance
“…In this study there was high CD133 expression in only 1 out of 16 triple negative cancers and which is in contrast to the study of Zhao et al CD133 expression was decreased in tumors with lymphovascular invasion, larger tumor size and higher stage. Martin et al [36] recently indicated that the CD133 expression is reduced in patients with metastatic disease, which supports our findings. On the other hand high CD133 expression was positively correlated with CD44 + and CD44 + /CD24 + expressions.…”
Section: Discussionsupporting
confidence: 94%
“…In this study there was high CD133 expression in only 1 out of 16 triple negative cancers and which is in contrast to the study of Zhao et al CD133 expression was decreased in tumors with lymphovascular invasion, larger tumor size and higher stage. Martin et al [36] recently indicated that the CD133 expression is reduced in patients with metastatic disease, which supports our findings. On the other hand high CD133 expression was positively correlated with CD44 + and CD44 + /CD24 + expressions.…”
Section: Discussionsupporting
confidence: 94%
“…Additionally, the expression of stem cell factors increased after CAF treatment in vitro, which relates to poor prognosis and increased risk of metastases. 24,25 Therefore, application of chemotherapy leads to a more mesenchymal tumor phenotype in this model. A mesenchymal phenotype of epithelial tumors corresponds to higher aggressiveness and poor prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with their essential role in cell adhesion to the extracellular matrix, dysregulation of integrin expression and their associated signalling pathways have been associated with pathological states such as carcinogenesis and the metastatic spread of tumor cells [44,45,46,47,48]. Although the above mentioned examples portray the complexity and dynamics of integrin-signalling, particularly in the context of carcinogenesis and tumor cell progression, interfering with integrin-ECM interactions appears to be an auspicious strategy for the development of therapeutic agents (Table 2).…”
Section: Interfering Integrin-ecm Interactions As a Potential Thermentioning
confidence: 99%
“…The α6-subunit is enriched in TICs in breast, prostate and colorectal cancers [44,46,49] as well as squamous cell carcinoma [48] and is important for the maintenance of glioblastoma stem cells [45]. Likewise, the expression of the β4-subunit has been described to serve as a marker for the propagation of lung cancer cells [50].…”
Section: Interfering Integrin-ecm Interactions As a Potential Thermentioning
confidence: 99%